HANDBALL DEVELOPMENT PROGRAM FOR CHILDREN: CREATING A HEALTHY AND ACCOMPLISHED GENERATION - Puriana, Ramadhany Hananto; Muhammad Wahyono; Angga Indra Kusuma; I Gede Dharma Utamayasa; Bayu Akbar Harmono; Ismawandi Bripandika Putra; Shandy Pieter Pelamonia (Journal of Social Comunity Services, 2025)
Objective: This study aims to evaluate the effectiveness of a handball development program for children in creating a healthy and accomplished generation. In addition, the program also teaches the value of sportsmanship and cooperation. Method: Although there are challenges in the implementation of the program, such as lack of facilities and parental support, collaboration between schools and communities can increase the success of the handball development program among children. Results: The participation of the government and schools in this program is necessary, in addition to improving cardiovascular ability, strength and coordination, the students will have good sportsmanship values, discipline and confidence. Novelty: This finding confirms the importance of sports development, especially handball, as a strategic step to form a healthier and more accomplished generation.